Pengaruh Gaya Kepemimpinan dan Kecerdasan Emosional Kepala Sekolah Terhadap Kinerja Guru TK Gugus Kecamatan Simpang Kanan Kabupaten Aceh Singkil - Ramadani, Sri; Putra, Mulia; Zahraini, Zahraini (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This study aims to analyze the influence of the leadership style and emotional intelligence of school principals on the performance of Gugus Kindergarten teachers, Simpang Kanan District, Aceh Singkil Regency. The type of research used in this research is quantitative descriptive type with survey methods. This research was carried out at Gugus Kindergarten, Simpang Kanan District, Aceh Singkil with a sample of 32 respondents. The sampling technique in this research used cluster proportional random sampling. The results of the analysis prove that there is a positive and significant influence of the principal's leadership style on the performance of the Simpang Kanan Aceh Singkil Kindergarten Teachers with a correlation coefficient value between these two variables of 0.713. There is a positive and significant influence of the principal's emotional intelligence on the job satisfaction of the Simpang Kanan Aceh Singkil Kindergarten Teacher with a correlation coefficient value between these two variables of 0.607. 3. There is a positive and significant influence on the principal's leadership style and the principal's emotional intelligence together on job satisfaction at the Gugus Simpang Kanan Aceh Singkil Kindergarten with a correlation coefficient value between these variables of 0.605.